Interrelationship between hypersensitivity to soybean proteins and growth performance in early-weaned pigs - D F Li; P G Reddy; Frank Blecha; R Klemm; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1990)
One hundred twenty-five pigs were orally infused with 6 g/d of either dried skim milk, soybean meal (48% CP), soy protein concentrate, extruded soy protein concentrate, or experimental soy protein concentrate from 7 to 11 d of age and then fed a diet containing the corresponding protein sources from weaning (d 21) to 35 d of age. All pigs were fed a corn-soybean meal diet containing 10% dried whey, 1.25% lysine, and 3% soybean oil for the remaining 21 d of the experiment. Skin-fold thickness following intradermal injection of protein extracts, xylose absorption, and anti-soy immunoglobulin G (IgG) titers were measured on d 6 postweaning. A total of 25 pigs (five pigs/treatment) was euthanized on d 7 postweaning. Villus height and crypt depth from duodenum samples were measured. These measurements were obtained to elucidate a relationship between the hypersensitivity responses to soybean products and growth performance of baby pigs. Pigs fed diets containing soybean meal had a lower rate of gain (ADG), lower villus height, higher serum anti-soy IgG titers, and increased skin-fold thickness following intradermal injection compared to those fed dried skim milk. Pigs fed other soy proteins also had lower ADG from d 0 to 14 postweaning; however, pigs fed moist-extruded soy protein concentrate tended to have higher ADG and improved feed utilization when compared to those pigs fed soybean meal. Skin-fold thickness and antisoy IgG titers were negatively correlated with ADG at d 14 postweaning. Results indicate that a model including skin-fold thickness and anti-soy IgG titers provided a good estimate of nursery pig growth performance (R2=.33). Villus height was related to ADG at d 14 postweaning (R2=.40). A combination of skin-fold thickness, anti-soy IgG titers, xylose absorption, villus height, and crypt depth provided the best estimate of growth performance (R2=.65) for early-weaned pigs.; Swine Day, Manhattan, KS, November 15, 1990
Keywords: Swine day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-189-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 610; Swine; Starter; Piglet; SBM; Soybean; Process; Performance